Development and field test of the Salutogenic Wellness Promotion Scale – short form (SWPS-SF) in U.S. college students. (March 2023) - Becker, Craig M.; Bian, Hui; Martin, Ryan J.; Sewell, Kerry; Stellefson, Michael; Chaney, Beth
Survey research is important for understanding health and improving practice among health professions. However, survey research can have drawbacks, such as overuse and excessively lengthy questionnaires that burden respondents. These issues lead to poor response rates and incomplete questionnaires. Low and incomplete response rates result in missing data and reduced sample size, damaging the value, usability and generalizability of the information collected. To address issues related to response rates and improve health research, shorter surveys are recommended because they impose less of a burden on respondents and are useful with larger populations. Health-related surveys also often focus on the factors leading to ill health without dedicating equal attention to factors supporting positive health. This study developed and tested a short form (SF) of the validated Salutogenic Wellness Promotion Scale (SWPS), which measures causes of health (rather than causes of disease), using responses from 2052 college students. The participants answered questions about their demographics and completed the SWPS and a perceived health assessment. Statistical tests demonstrated the SWPS-SF had significant relationships with the full SWPS, health status, and Grade Point Average (GPA). Statistical tests were also used to establish cutoff scores that had a high true positive and low false negative rate. These cutoff scores demonstrated a relationship of higher performance and better health. These promising results suggest this short test can provide valid information without burdening the respondents. Authors recommend additional tests be completed to validate the SWPS-SF.